Myasthenia Gravis in Pregnancy: A Case Report - Sebastian Berlit; Benjamin Tuschy; Saskia Spaich; Marc Sütterlin; Regine Schaffelder (Case Reports in Obstetrics and Gynecology)
Objective. To present a case of maternal myasthenia gravis in pregnancy and give a systematic review of the literature. Case. We report the case of a 38-year-old parturient with a life-threatening complication of immune-mediated myasthenia gravis shortly after an elective cesarean section on patient's request under spinal anesthesia at 35 + 3 weeks of gestation. The newborn was transferred to the pediatric unit for surveillance and did not show any signs of muscular weakness in the course of time. The mother developed a respiratory insufficiency on the second day postpartum. The myasthenic crisis led to a progressive dyspnoea within minutes, which exacerbated in a secondary generalized seizure with cardiac-circulatory arrest. After successful cardiopulmonary resuscitation, the patient was transferred to intensive care. The interdisciplinary therapeutic approach included ventilatory assistance via endotracheal intubation, parenteral pyridostigmine, azathioprine, and steroids. By interdisciplinary measures, a stable state was regained. Conclusion. Myasthenia gravis especially when associated with pregnancy is a high-risk disease. As this disease predominantly occurs in women of reproductive age, it is important to be aware of this condition in obstetrics and its interdisciplinary diagnostic and therapeutic management.